FUS-ion (Function, University, Scale) for arterial road design: Bringing together traffic and place functions - Tiwari, Reena; Curtis, Carey (Omnipress, 2012)
There is an emerging practice in urban arterial design which seeks to shift the focus from segregating different users of the street to integrating them. In this respect the integration of traffic and place functions is identified as the way forward. After a review of the US design models - Complete Streets Smart Codes, Context Sensitive Solutions (CSS) and Quilt-Net approach, this paper using a functional, physical and social evaluation approach to urban arterials, proposes a model for arterial classification. Drawing on our research based in Perth, we present a classification and design model ‘FUS-ion’ (Function, Universality, Scale) based on a management tool proposed by Curtis and Tiwari (2008) which we have subsequently refined and further developed after its application on an existing urban arterial segment in Perth, Australia. This model brings together three key dimensions of Transport, Built-form and People. It responds to varying scales ranging from street segment to metropolitan thoroughfares and is geared to be used as a tool to manage the arterial system, both within an existing urban framework as well as for the planning of new developments.